Strategi Penerjemahan Istilah Budaya dalam Terjemahan Bahasa Inggris Novel Bumi Manusia Karya Pramoedya Ananta Toer - Ibadurrohman, Ridwan (Kementerian Sekretariat Negara Republik Indonesia, 2019)
This research aims to analyze the strategies used for translating cultural terms in English translation of novel Bumi Manusia written by Pramoedya Ananta Toer. The research employs the theory put forward by Newmark (1988) which divides cultural elements into five categories: Ecology, material culture, social culture, social organization and gestures and habits. The research also employs the theory explained by Baker (2009) and Newmark (1988) which describe several translation strategies commonly used by translators, including transference, naturalization, cultural equivalent, functional equivalent, additional explanation, and reduction. Researcher also uses other sources, including books and journals on history and culture, to deepen understanding of the context of the cultural terms contained in ST, as well as their translation in TT. Based on the analysis, it turns out that the strategy most widely used in translating cultural terms in Bumi Manusia is transference, followed by additional explanation, functional equivalent, reduction and cultural equivalent. Keywords: literary translation, novel, cultural terms, translation strategies.